KINERJAPENGEMUDIDITINJAUDARIERGONOMIKAFISIKDANLINGKUNGAN - , SANNY HAHURY,ST ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Transportation is a very important tool to facilitate strategic and economic cycle, so the transportation is necessary in creating the movement of people and goods efficiently and effectively. Driving the distance is quite far and have a workload that is beyond a persons physical and ergonomic working environment can affect the comfort of work, psychological health, productivity and performance rather than the driver. This study aims to identify the physical ergonomic factors and environmental factors influencing the performance of the driver. The sample used in this study are trans yogya bus driver with the driver line 1A by the number of 22 people. Measurements were performed using a pulse measuring instrument, reaction time, fatigue, noise, vibration, temperature and performance. The method used in this research is the multiple linear regression. The results showed that the workload of the driver based on pulse, fatigue, reaction time and the noise is still within the normal ranges and did not exceed the threshold value. As for the temperature and vibration exceeds the threshold value. Based on multiple linear regression equation shows only the vibrations that have a significant effect on performance, while the other variables are not significant.